Analisis Pengaruh Keberagaman Dewan Komisaris dan Struktur Kepemilikan Perusahaan terhadap Kualitas Pengungkapan Corporate Social Responsibility - Triani Triani (Jurnal Ilmiah Aset, 2018)
This study aimed to examine the quality of CSR disclosure of public companies listed in BEI influenced by the diversity of the board of commissioners and ownership structure of the company. This study used 53 companies as a sample and observed for four years of from 2013-2016, so the total observations in this study as many as 212 annual reports of the companies. The result showed that only government share ownership variable (X4) that had a positive effect on CSR quality variable (Y). Meanwhile, proportion of female membership in the board of commissioners (X1), proportion of foreign membership in the board of commissioners (X2), and foreign ownership (X3) did not affect the quality of CSR disclosure (Y).